Quantifying green innovation: A bibliometric analysis of deep eutectic solvents and applications as eco-friendly solvents - Muhammad Nawaz; Muhammad Irfan; Khadija Zahra; Humbul Suleman; Mohamad Azmi Bustam; Abdulhalim Shah Maulud (Journal of Ionic Liquids, 2025)
Deep eutectic solvents (DESs) have emerged as a promising class of green solvents, with various advantages over traditional organic solvents and ionic liquids. This study presents a comprehensive bibliometric analysis of research trends and developments in applying DES as eco-friendly solvents. Using data from the Web of Science database, 2,262 research articles were analyzed from 2009 to 2023. The analysis reveals a significant increase in DES-related publications, growing from fewer than 20 articles per year in 2011 to more than 500 articles annually by 2023, reflecting the rising interest in this green chemistry field. Geographical and institutional distribution was assessed using a novel performance metric, the Research Impact Score (RIS), which integrated total publications, citations, citations per publication, and h-index. China is the leading contributor, with 863 publications and 28,944 citations with RIS of 0.86. Mjalli, Farouq S., from Sultan Qaboos University, Oman, leads in total publications (38) and total citations (3,166) with an outstanding RIS of 0.91. Universiti Malaya, Malaysia, emerges as the most balanced and impactful institution with a high publication output (49), the highest total citations (3,741), and a leading RIS of 0.98. ''Journal of Molecular Liquids'' emerged as the most active publishing source related to DES research, with 205 articles. Moreover, DESs demonstrated superior extraction efficiency, particularly in bioactive compounds such as phenolics and flavonoids. These findings underscore the innovative potential of DESs in advancing sustainable chemical practices and providing valuable insights into future research directions, aiming to further develop and apply DESs across various scientific and industrial fields.